PENGARUH PPh PASAL 21 MASA TERHADAP JUMLAH PAJAK YANG DISETOR PADA PT. DETECON ASIA-PACIFIC LTD - Aisyah, Nurul (Universitas Bina Sarana Informatika, 2015)
Tax provide an important role for financial source of revenue countries, the government issued laws and regulations that aims to regulate the implementation of taxation in the community. The contribution of tax has a very large for the state revenues. Tax is that most important thing in the state revenues, article 21 income tax is a tax on income in form of salary, wages, emoluments, the allowance, and other payment by the name and in the form of anything with respect to work in any form in connection with work or office, service, and activity undertaken by private persons subject to taxation in the country. In this research the authors found that 21 income tax have no influence significantly, where the value of significant 0,63 > 0.05 (larger 0.05 of income tax and article 21 the no impact on the amount of tax in setor on PT. Detecon Asia-Pacific LTD. The level of the close or relation of income tax 21 with the total tax passed on PT. Detecon Asia-Pacific LTD. The level of keeratan or relationships with a total number of 21 income tax taxes are deposited on PT. Detecon Asia-Pacific LTD. which is a fairly high correlation which 084 and relationships are expressed in percentages of 9.16% (the value of the determination). Keywords: Receipts from income tax article 21, Tax Paid